Prevalence of Chlamydia pneumoniae antibodies in patients with acute respiratory infections in Israel. Issue 3 (March 1994) - Ben-Yaakov, M; Lazarovich, Z; Beer, S; Levin, A; Shoham, I; Boldur, I
Abstract : AIMS--To evaluate the prevalence of antibodies to Chlamydia pneumoniae (TWAR) in relation to other aetiological agents of acute respiratory infections in Israeli patients. METHOD--Serum samples from 604 patients (183 children and 421 adults) were collected over three years. Antibodies to C pneumoniae, C trachomatis, and Legionella sp were evaluated using the microimmunofluorescence (MIF) assay. Antibodies to Mycoplasma pneumoniae were detected using the Serodia Myco II test. RESULTS--Antibodies to TWAR were detected in 319 (51.3%) sera. Twenty one patients had MIF results indicative of recent infection. TWAR prevalence and antibody titres in children (aged 1-10 years) were low, gradually increased in teenagers (11-18 years), and were highest in adults and elderly patients. In contrast to the consistently noted TWAR antibody prevalence and serological evidence of recent infection during the study period, a significant decrease in those variables was recorded for C trachomatis. Six patients had serological evidence of recent infection with both C pneumoniae and C trachomatis. The presence of antibodies to Mycoplasma pneumoniae and Legionella sp was tested in 473 of the patients; 29 had antibodies to M pneumoniae and 23 to Legionella sp. Six patients (including five children) had serological evidence of recent infection with M pneumoniae and four with Legionella sp. CONCLUSION--C pneumoniae should be considered in patients with acute respiratory diseases. MIF is the preferred method for monitoring the presence of antibodies to this organism.